DNA microarray‐based analysis of voluntary resistance wheel running reveals novel transcriptome leading robust hippocampal plasticity. Issue 11 (20th November 2014) - Lee, Min Chul; Rakwal, Randeep; Shibato, Junko; Inoue, Koshiro; Chang, Hyukki; Soya, Hideaki
Abstract In two separate experiments, voluntary resistance wheel running with 30% of body weight (RWR), rather than wheel running (WR), led to greater enhancements, including adult hippocampal neurogenesis and cognitive functions, in conjunction with hippocampal brain‐derived neurotrophic factor (BDNF) signaling (Lee et al., J Appl Physiol, 2012; Neurosci Lett., 2013). Here we aimed to unravel novel molecular factors and gain insight into underlying molecular mechanisms for RWR‐enhanced hippocampal functions; a high‐throughput whole‐genome DNA microarray approach was applied to rats performing voluntary running for 4 weeks. RWR rats showed a significant decrease in average running distances although average work levels increased immensely, by about 11‐fold compared to WR, resulting in muscular adaptation for the fast‐twitch plantaris muscle. Global transcriptome profiling analysis identified 128 (sedentary × WR) and 169 (sedentary × RWR) up‐regulated (>1.5‐fold change), and 97 (sedentary × WR) and 468 (sedentary × RWR) down‐regulated (<0.75‐fold change) genes. Functional categorization using both pathway‐ or specific‐disease‐state‐focused gene classifications and Ingenuity Pathway Analysis (IPA) revealed expression pattern changes in the major categories of disease and disorders, molecular functions, and physiological system development and function. Genes specifically regulated with RWR include the newly identified factors of NFATc1, AVPR1A, and FGFR4, as well as previously known factors, BDNF and CREB mRNA. Interestingly, RWR down‐regulated multiple inflammatory cytokines (IL1B, IL2RA, and TNF) and chemokines (CXCL1, CXCL10, CCL2, and CCR4) with the SYCP3, PRL genes, which are potentially involved in regulating hippocampal neuroplastic changes. These results provide understanding of the voluntary‐RWR‐related hippocampal transcriptome, which will open a window to the underlying mechanisms of the positive effects of exercise, with therapeutic value for enhancing hippocampal functions.